BEST VITELLIFORM MACULAR DYSTROPHY IN AFGHAN TWINS - Kausar, Ayisha; Akhtar, Nadia (Journal of Ayub Medical College Abbottabad, 2016)
Best vitelliform macular dystrophy is the second most common type of hereditary fundus dystrophies. Our case report describes twin brothers of Afghan family who developed Best vitelliform macular dystrophy. One of them developed choroidal neovascularization in one eye which was treated with single intravitreal injection of bevacizumab. The patient showed stable vision and did not have any recurrence until 3 years of follow up. Many cases of familial Best vitelliform macular dystrophy have been described in medical literature but our report is unique as it presents twin brothers with Best vitelliform macular dystrophy which has never been described before. Keywords: Best vitelliform macular dystrophy, Choroidal neovascularization, Optical coherence tomography